Assessing the Impact of Laboratory Information System on Clinical Workflow and Patient Outcomes - Antonio, Stephanie M.; Dancel, May B.; Lim , Celestine N.; Roberto, Juan Rodrigo A.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study looks at how Valenzuela Medical Center's (VMC) clinical workflow efficiency and patient outcomes are influenced by the installa-tion of a Laboratory Information System (LIS). Due to time constraints, convenience sampling was used to collect data from sixty-three (63) medical professionals in the clinical and diagnostic laboratory depart-ments using a descriptive study design and a mixed-methods technique. To measure participant responses, descriptive statistics such as means, standard deviations, and frequency distributions were used. Using paired sample t-tests, inferential analysis was carried out to compare metrics before and after LIS adoption, with an emphasis on factors like error rates, turnaround times, and specimen handling accuracy.Key findings showed that LIS adoption improved data accessibility across departments, lowered transcription errors by about 28%, and cut specimen processing turnaround times by an average of 35%, all of which contributed to improved interdepartmental communication. Further-more, 90% of respondents expressed more confidence in the accuracy of laboratory results following LIS integration, and 85% of respondents re-ported higher satisfaction with data processing procedures. Significant improvements were also shown in patient outcomes, with quicker diag-nostic processing leading to earlier treatment commencement and, in some situations, shorter hospital stays overall. In addition to demon-strating the wider advantages of incorporating cutting-edge information systems in healthcare settings, this study emphasizes the critical role that LIS plays in improving laboratory operations, cutting down on diag-nostic delays, and improving the quality of patient care at VMC.